Performance analysis for cloud query encryption - Ali Raheem, Zainalabideen; Mohd Aman, Azana Hafizah; Islam, Shayla; Hassan Abdalla Hashim, Aisha (Institute of Electrical and Electronics Engineers Inc., 2019)
The clouds computing comprises of information inquiry benefits that is versatile and adaptable in costing. Cloud purchasers ordinarily put away secret or fragile information that required to be sheltered and verified. Accordingly, delicate information is encoded for security and classification. A few contemplates have proposed Advanced Encryption Standard (AES) as well as Rivest Shamir Adleman (RSA) encryption techniques to protect cloud information wellbeing and secureness. However, every encryption strategy gives a particular degree of security which accompanies a contrary degree of proficiency. Henceforth, this exploration will examinations the presentation for both encryption techniques. The exploration arrangement includes Microsoft SQL Server as cloud database reenactment, and a Visual Studio stage to recreate the neighborhood questions. The examination is accomplished for encryption and unscrambling mystery quality. In general, the outcomes showed up are not noteworthy as every strategy has its own advantages.